New Viscoelastic Hydrogel Hymovis MO.RE. Single Intra-articular Injection for the Treatment of Knee Osteoarthritis in Sportsmen: Safety and Efficacy Study Results - Bernetti, Andrea; Agostini, Francesco; Alviti, Federica; Giordan, Nicola; Martella, Federica; Santilli, Valter; Paoloni, Marco; Mangone, Massimiliano (Frontiers in Pharmacology, 2021)
Viscosupplementation by hyaluronic acid (HA) is recommended for non-surgical management of knee osteoarthritis (OA). This study investigated the efficacy and safety of a single i.a. (32mg/4ml) Hymovis MORE injection, a new HA derivative hydrogel, for the treatment of adult regular sport players affected by knee OA arising from overuse injuries. Patients were prospectively enrolled if regularly practicing sports and being diagnosed with Kellgren-Lawrence grade I-III OA. They received a single Hymovis MORE intra-articular (i.a.) injection and were evaluated 30, 90, 180 and 360 days thereafter. Assessment involved measuring changes in knee function, pain, activity of daily living (ADL) and quality of life (QOL) by using the Knee injury and Osteoarthritis Outcome Score (KOOS), GAIT analysis, the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores for knee pain (WOMAC A) and function (WOMAC C), and a visual analogue scale (VAS) pain score. The study involved thirty-one patients, 23 women and 8 men, whose median age was 49. KOOS function subscore, as well as GAIT cadence and velocity showed a statistically significant increase at each time-point after injection (p<0.0001). WOMAC, KOOS pain, symptoms, ADL and QOL scores also significantly improved at all control visits. No severe adverse events or treatment-related events were detected. A single Hymovis MORE (32mg/4ml) intra-articular injection provides a rapid, lasting and safe response in regular sport players affected by knee OA, possibly representing a viable therapeutic option for this demanding patient subgroup. Further investigations are necessary to confirm these findings.